Effect of long‐term valproic acid therapy on lipid profiles in paediatric patients with epilepsy: a meta‐analysis. Issue 5 (3rd November 2022) - Guo, Hong‐Li; Dong, Na; Chen, Feng; Zeng, Yuan‐Yuan; Hu, Ya‐Hui; Xia, Ying; Tian, Man; Lu, Xiao‐Peng; Qiu, Jin‐Chun
Abstract: Objective . Despite the potential role of valproic acid (VPA) in weight gain, the effects of VPA therapy on lipid profiles remain unclear. This study aimed to review the influence of VPA therapy on serum lipid profiles in children with epilepsy. Methods . This meta‐analysis was conducted on data from PubMed, Web of Science, Cochrane Library, and Embase databases. Case‐controlled studies, which assessed the effects of VPA therapy on lipid profiles, were included. All outcomes were recorded as continuous variables, and the effect size was measured. Results . VPA therapy was associated with a significant reduction in total cholesterol (mean difference [MD]=‐6.34, 95% confidence interval [CI]: ‐12.30, ‐0.37, p =0.04) and low‐density lipoprotein cholesterol levels (MD = ‐7.75, 95% CI: ‐13.48, ‐2.0, p =0.008). No significant effects were observed regarding the levels of high‐density lipoprotein cholesterol and triglycerides. Significance . In conclusion, this meta‐analysis indicates that VPA therapy causes a decrease in the levels of total cholesterol and low‐density lipoprotein cholesterol.